Improving selection of documents for auditing by Fin Ware Quality Control Team - Dacquel, Zaneta Louise P. (Animo Repository, 2017)
An inefficient process within a vital team causes workflow disruption between and among company departments, delay in product release, and inefficiency in the workplace thereby heightening the threat of potential loss of clients and stagnancy of the company. Thus, the need to improve the process within the Quality Control team to enable timely release of financial information to clients is imperative as this will facilitate and aid the clients with their business strategies and enhance their investment decisions. FinWare represents a Company engaged in providing clients with financial information and analytics. This action research paper aims to address the issue on inefficient selection of documents for audit as caused by the lack of an established selection process in the Quality Control team of FinWare Philippines Inc. The Action Research Cycle of Coghlan and Brannick was utilized as a guide through the course of this study. Methods of inquiry and collaboration with the Quality Control team and Operations team were conducted throughout the action research cycles to gather and analyze the data. The DMAIC framework was followed to deal with the change process and ensure sustainable results. After two action research cycles, I and my colleagues created an effective tracker to aid the Quality Control Associates in the proper selection of document. We also established a selection process guideline to remove non-value adding activities in the selection process within our Quality Control team. On a broader context, this action research paper contributes to the larger society through the synthesis of management theories and concepts, personal reflections and learnings, and social development principles, in order to create relevance to other organizations that are yet to undergo a similar process of change for quality management.